2011
DOI: 10.1051/0004-6361/201015863
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the extinction law in the Trifid nebula

Abstract: Context. In the past few years, the extinction law has been measured in the infrared wavelengths for various molecular clouds and different laws have been obtained. Aims. In this paper we seek variations of the extinction law within the Trifid nebula region. Such variations would demonstrate local dust evolution linked to variation of the environment parameters such as the density or the interstellar radiation field. Methods. The extinction values, A λ /A V , are obtained using the 2MASS, UKIDSS and Spitzer/GL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 51 publications
5
94
1
Order By: Relevance
“…Rho et al (2008) reviewed literature values between 1.68 and 2.84 kpc and adopted a distance of about 1.7 kpc. Cambrésy et al (2011) found 2.7 ± 0.5 kpc in their analysis of new near-and mid-infrared data. Torii et al (2011) used both 1.7 and 2.7 kpc in their discussion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rho et al (2008) reviewed literature values between 1.68 and 2.84 kpc and adopted a distance of about 1.7 kpc. Cambrésy et al (2011) found 2.7 ± 0.5 kpc in their analysis of new near-and mid-infrared data. Torii et al (2011) used both 1.7 and 2.7 kpc in their discussion.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, there are almost no close binaries amongst the magnetic intermediate-mass main-sequence Ap-type stars (e.g. Carrier et al 2002). Since this is expected if they were merger products, this argues for the binary hypothesis of the field origin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, large scale surveys at nearand mid-IR wavelength (2MASS, UKIDSS and GLIMPSE) have provided new insights into the extinction behavior of dust deep inside dense clouds by probing the colors of background stars. These studies have revealed that the near-IR extinction law shows a flattening in dense cores, typically at depths corresponding to an A V of ∼20 mag (Indebetouw et al 2005;Chapman et al 2009;Cambrésy et al 2011) indicative of grain growth A&A 532, A43 (2011) (Weingartner & Draine 2001). Recently, too, near-IR scattered light has been detected from dense cloud cores and this is indicative of grain growth to micron-sizes Steinacker et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, widefield extinction maps obtained by near-IR colorexcess techniques cover a wider range of column densities, typically from N(H + H 2 ) ∼ 0.1−40 × 10 21 cm −2 (Lada et al 1994;Lombardi & Alves 2001;Lombardi 2009;Cambrésy et al 2011Cambrésy et al , 2013Rowles & Froebrich 2009;Schneider et al 2011). Some major results obtained from these studies are, for example, that there is a relation between the rate of star formation and the amount of dense gas in molecular clouds , that a universal threshold in visual extinction of A v ≈ 6 mag for the formation of stars could exist (Froebrich & Rowles 2010), and that there are characteristic size scales in molecular clouds, indicating the dissipation and injection scales of turbulence (Schneider et al 2011).…”
Section: Introductionmentioning
confidence: 99%